The "Burden” Or What It Means to Be Black in America Today - Khedhir, Yesmina (Hungarian Journal of English and American Studies, 2020)
Book review:Riley, Rochelle, ed. The Burden: African Americans and the Enduring Impact of Slavery. Detroit: Wayne State UP, 2018. 178 pages. ISBN 978-0-8143-4514-6. Hb. Npr.